The Influence of Management Information System Effectiveness and Users’ Technical Competence on Individual Performance at PT Pindad Enjinering Indonesia (PT PEI) - Vira Putri Febriyani; Listri Herlina; Wendi Yuliawan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of Management Information System (MIS) effectiveness and users’ technical competence on individual performance among employees of PT Pindad Enjiniring Indonesia (PT PEI). The company aims to enhance employee performance through the optimization of an integrated management information system and the development of users’ technical capabilities. The research employs a verificative method using a total population survey approach (n = 32), with data collected through a Likert-scale questionnaire. Data analysis was carried out using multiple linear regression, supported by validity, reliability, classical assumption tests, t-test, F-test, and the coefficient of determination (R²). The results reveal that MIS effectiveness significantly influences individual performance by 34.16%, users’ technical competence contributes 38.94%, and both variables simultaneously affect individual performance by 73.1%, while the remaining 26.9% is attributed to other factors not examined in this study. These findings highlight that enhancing MIS effectiveness and users’ technical competence plays a vital role in improving individual employee performance within the manufacturing industry context.